Dopant‐Dependent Stability of Garnet Solid Electrolyte Interfaces with Lithium Metal. Issue 12 (10th February 2019) - Zhu, Yisi; Connell, Justin G.; Tepavcevic, Sanja; Zapol, Peter; Garcia‐Mendez, Regina; Taylor, Nathan J.; Sakamoto, Jeff; Ingram, Brian J.; Curtiss, Larry A.; Freeland, John W.; Fong, Dillon D.; Markovic, Nenad M.
Abstract: Li7 La3 Zr2 O12 (LLZO) garnet‐based materials doped with Al, Nb, or Ta to stabilize the Li + ‐conductive cubic phase are a particularly promising class of solid electrolytes for all‐solid‐state lithium metal batteries. Understanding of the intrinsic reactivity between solid electrolytes and relevant electrode materials is crucial to developing high voltage solid‐state batteries with long lifetimes. Using a novel, surface science‐based approach to characterize the intrinsic reactivity of the Li–solid electrolyte interface, it is determined that, surprisingly, some degree of Zr reduction takes place for all three dopant types, with the extent of reduction increasing as Ta < Nb < Al. Significant reduction of Nb also takes place for Nb‐doped LLZO, with electrochemical impedance spectroscopy (EIS) of Li||Nb–LLZO||Li symmetric cells further revealing significant increases in impedance with time and suggesting that the Nb reduction propagates into the bulk. Density functional theory (DFT) calculations reveal that Nb‐doped material shows a strong preference for Nb dopants toward the interface between LLZO and Li, while Ta does not exhibit a similar preference. EIS and DFT results, coupled with the observed reduction of Zr at the interface, are consistent with the formation of an "oxygen‐deficient interphase" (ODI) layer whose structure determines the stability of the LLZO–Li interface. Abstract : Understanding reactivity at buried interfaces is crucial to developing next‐generation solid‐state batteries. A novel, surface science‐based approach reveals that contact with Li metal yields Zr reduction in Nb‐, Ta‐, and Al‐doped Li7 La3 Zr2 O12, with reduction increasing as Ta < Nb < Al. This Zr reduction indicates the formation of an "oxygen‐deficient interphase, " whose composition determines the stability of the Li– Li7 La3 Zr2 O12 interface.